CCR7 Guides Migration of Mesenchymal Stem Cell to Secondary Lymphoid Organs: A Novel Approach to Separate GvHD from GvL Effect. (July 2014) - Li, Hong; Jiang, YanMing; Jiang, XiaoXia; Guo, XiMin; Ning, HongMei; Li, YuHang; Liao, Li; Yao, HuiYu; Wang, XiaoYan; Liu, YuanLin; Zhang, Yi; Chen, Hu; et al.
Abstract Inefficient homing of systemically infused mesenchymal stem cells (MSCs) limits the efficacy of existing MSC‐based clinical graft‐versus‐host disease (GvHD) therapies. Secondary lymphoid organs (SLOs) are the major niches for generating immune responses or tolerance. MSCs home to a wide range of organs, but rarely to SLOs after intravenous infusion. Thus, we hypothesized that targeted migration of MSCs into SLOs may significantly improve their immunomodulatory effect. Here, chemokine receptor 7 (CCR7) gene, encoding a receptor that specifically guides migration of immune cells into SLOs, was engineered into a murine MSC line C3H10T1/2 by retrovirus transfection system (MSCs/CCR7). We found that infusion of MSCs/CCR7 potently prolonged the survival of GvHD mouse model. The infused MSCs/CCR7 migrate to SLOs, relocate in proximity with T lymphocytes, therefore, potently inhibited their proliferation, activation, and cytotoxicity. Natural killer (NK) cells contribute to the early control of leukemia relapse. Although MSCs/CCR7 inhibited NK cell activity in vitro coculture, they did not impact on the proportion and cytotoxic capacities of NK cells in the peripheral blood of GvHD mice. In an EL4 leukemia cell loaded GvHD model, MSCs/CCR7 infusion preserved the graft‐versus‐leukemia (GvL) effect. In conclusion, this study demonstrates that CCR7 guides migration of MSCs to SLOs and thus highly intensify their in vivo immunomodulatory effect while preserving the GvL activity. This exciting therapeutic strategy may improve the clinical efficacy of MSC based therapy for immune diseases. Stem Cells2014;32:1890–1903